Identificación de patrones histopatológicos en perros con dermatopatías no neoplásicas atendidos en veterinaria Anubis. - Alcivar Espinales, Andrea Estefania (Machala : Universidad Técnica de Machala, 2024)
The histopathological pattern constitutes an effective tool for a correct knowledge of the degree of lesion present in the skin of canines. The research was developed with the objective of identifying histopathological patterns of cutaneous inflammation in dogs with non-neoplastic dermatopathies treated in the veterinary clinic Anubis, Machala, province of El Oro, in the period from November 2023 to January 2024, for this purpose, 22 canines of different breeds were sampled and the techniques of skin scraping, imprinting, Cook's tape were applied, and after a lesion was detected, a punch biopsy was performed. The association between the breeds and the causal agents of dermatopathologies with the histopathological patterns found was established by means of multiple correspondence analysis, where a greater closeness of the categories of the variables evidences a greater predilection to suffer the cutaneous pathology. Pyodermas and dermatomycosis were the main dermatopathologies found in the canines studied and the Doberman Pincher, American Bullyng, French Poodle, Pitbull and Chihuahua breeds presented a greater predisposition to suffer the DPSP histopathological pattern, mostly associated to adult animals. The causative agents Bacteria (Pyodermas) and Fungi (Malassezia and Dermatophytes) presented the highest frequency of involvement. The histopathological pattern DPSP was found to be highly associated with the presence of Pyodermas. Three histopathological patterns of non-neoplastic dermatopathies were found in the period studied, including DPSP, PFF and DND. The histopathologic pattern of non-neoplastic dermatopathies with the highest frequency of occurrence in the sample studied was superficial and deep perivascular dermatitis.
En patrón histopatológico constituye una herramienta eficaz para un correcto conocimiento del grado de lesión presente en la piel de caninos. La investigación se desarrolló con el objetivo de identificar patrones histopatológicos de inflamación cutánea en perros con dermatopatías no neoplásicas atendidos en la clínica veterinaria Anubis, Machala, provincia de El Oro, en el periodo de noviembre de 2023 a enero de 2024, para ello, se muestrearon 22 caninos de diferentes razas y se aplicaron las técnicas de raspado cutáneo, impronta, cinta de Cook, y posteriormente de detectada una lesión se procedió a realizar la Biopsia con Punch. La asociación entre las razas y los agentes causales de dermatopatías con los patrones histopatológicos encontrados se estableció mediante análisis de correspondencia múltiple, donde una mayor cercanía de las categorías de las variables evidencia una mayor predilección a padecer la patología cutánea. Las piodermas y dermatomicosis fueron las principales dermatopatías encontradas en los caninos estudiados y las razas Dóberman Pincher, American Bullyng, French Poodle, Pitbull y Chihuahua presentaron una mayor predisposición a padecer el patrón histopatológico DPSP, asociado mayormente a animales adultos. Los agentes causales Bacterias (Piodermas) y Hongos (Malassezia y Dermatofitos) presentaron la mayor frecuencia de afectación. El patrón histopatológico DPSP se encontró altamente asociado con la presencia de Piodermas. En el período estudiado se encontraron tres patrones histopatológicos de dermatopatías no neoplásicas, entre las que se encuentran DPSP, PFF y DND. El patrón histopatológico de dermatopatías no neoplásicas con mayor frecuencia de aparición en la muestra estudiada fue la dermatitis perivascular superficial y profunda.
Keywords: DERMATITIS; CANINOS; PIODERMAS; DERMATOMICOSIS